Method for evaluating coke quality deterioration degree in hydrogen-rich smelting process of blast furnace
By conducting dissolution experiments and slag-iron permeable coking experiments under hydrogen-rich smelting conditions in blast furnaces, and quantitative evaluation of cokes combined with comprehensive indexes, the problem of difficulty in evaluating the degree of coke quality deterioration and matching with furnace materials in the existing technology is solved, and a comprehensive and accurate analysis of coke performance is achieved.
Patent Information
- Application Number
- CN202510051332.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to comprehensively and accurately evaluate the degree of quality deterioration of coke under hydrogen-rich smelting conditions of blast furnaces and its matching with the furnace charge, which makes it difficult to scientifically quantify the changes in the dissolution behavior and mechanical properties of coke.
The performance of coke was quantitatively evaluated by performing dissolution experiments and slag-iron coking experiments under simulated hydrogen-rich atmosphere conditions in blast furnaces, combined with the weight loss rate, strength retention rate and breathability comprehensive index.
A comprehensive and accurate quantitative analysis of the dissolution behavior and mechanical properties of coke in a hydrogen-rich atmosphere is achieved, which can quantify the reaction resistance, mechanical properties and breathability of coke, and evaluate its matching with the furnace material.
Smart Images

Figure CN119845777A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of blast furnace ironmaking technology, and in particular to a method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process. Background Art
[0002] Blast furnace ironmaking process is an important part of steel production, in which coke plays a vital role in the blast furnace as a reducing agent, heat source and material column skeleton. As the steel industry develops towards green and low-carbonization, hydrogen-rich smelting technology has gradually become a key path for low-carbon transformation of blast furnaces. By introducing reducing gases such as hydrogen into the blast furnace, carbon emissions can be effectively reduced. However, the introduction of hydrogen-rich atmosphere places higher requirements on the performance of coke in blast furnace operation.
[0003] Under hydrogen-rich smelting conditions, coke will be subjected to the strong reaction of hydrogen and water vapor, and its quality deterioration rate will be significantly accelerated. This degradation is manifested in the loss of coke mass, increased porosity and decreased mechanical strength, which has an adverse effect on the permeability, slag iron fluidity and material column stability in the blast furnace. In the prior art, the evaluation method for coke performance is mainly focused on conventional blast furnace conditions, and the impact of hydrogen-rich environment on the various performance of coke is not fully considered. In addition, the evaluation index of coke performance in the prior art is relatively single, and it is difficult to fully reflect the overall performance of coke under the combined effects of high temperature and slag iron.
[0004] Due to the lack of a systematic evaluation method, it is difficult for existing technologies to scientifically quantify the dissolution behavior and mechanical property changes of coke in a hydrogen-rich atmosphere, and it is also difficult to effectively evaluate the compatibility of coke with blast furnace charges. Therefore, a comprehensive analysis method for coke performance under blast furnace hydrogen-rich smelting conditions needs to be improved urgently to provide a reliable basis for coke selection and optimization of blast furnace operating parameters. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for evaluating the degree of quality deterioration of coke during blast furnace hydrogen-rich smelting, which can comprehensively and accurately evaluate the quality deterioration characteristics of coke under blast furnace hydrogen-rich smelting conditions and its matching with furnace charge.
[0006] To achieve the above object, the present invention is implemented by the following technical scheme: A method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process comprises the following steps:
[0007] Under the conditions of simulating the hydrogen-rich atmosphere of a blast furnace, a dissolution test device is used to perform a gasification reaction on the coke sample, the mass loss of the coke sample is controlled to reach a set range, and the coke sample after the reaction is obtained;
[0008] The coke samples after reaction were subjected to slag iron coke penetration test using slag iron coke penetration test device to measure the permeability, slag iron dripping time and strength retention rate of the coke coke penetration process;
[0009] Based on the data obtained from the dissolution test and the slag iron coke penetration test, the coke performance was quantitatively evaluated using the coke weight loss rate, strength retention rate and permeability comprehensive index.
[0010] Preferably, the dissolution experiment device comprises:
[0011] A high temperature furnace, in which a hanging basket for accommodating coke samples is arranged, and a gas mixing device is connected to the outside;
[0012] Thermobalance, which is set on the top of the high-temperature furnace and connected to the hanging basket, is used to measure the mass change of the coke sample in real time;
[0013] A first gas supply system, comprising a plurality of gas sources and a water vapor generator, wherein the first gas supply system is connected to a gas mixing device via a pipeline;
[0014] A gas mixing device is provided between the first gas supply system and the high temperature furnace, and is used to mix each gas source and water vapor and then transport them to the high temperature furnace;
[0015] The control system is connected with the high temperature furnace and the gas supply system to control the temperature, atmosphere composition and flow rate.
[0016] Preferably, the dissolution experiment comprises the following steps:
[0017] The coke sample is placed in the hanging basket of the dissolution experiment device and a protective atmosphere is set;
[0018] At a predetermined temperature, a mixed gas is introduced, wherein water vapor is provided by a water vapor generator and mixed with other gases;
[0019] The mass change of the coke is recorded in real time. When the weight loss rate reaches a predetermined value, the experiment is stopped and the coke is cooled for future use.
[0020] Preferably, the slag iron coking experimental device comprises:
[0021] A high-temperature coke oven, in which a crucible for containing coke samples and slag-iron mixture is arranged;
[0022] A perforated crucible with a coke hole at the bottom for placing the layered coke sample and the slag-iron mixture above it;
[0023] Pressure sensor, used to monitor the pressure difference of the coke layer in real time;
[0024] The data acquisition device is connected with the pressure sensor and the temperature control system to record the pressure change of the material layer, the temperature and time of the slag dripping;
[0025] The second gas supply system is used to provide a protective atmosphere and is connected to the high-temperature coke oven through a pipeline;
[0026] The temperature control system is connected to the high-temperature coke oven and is used to control the heating rate and experimental temperature.
[0027] Preferably, the slag iron coking experiment comprises the following steps:
[0028] The dissolved coke sample is spread in layers in a perforated crucible;
[0029] A mixture of metallic iron powder and pre-melted slag powder is laid on top of the coke sample;
[0030] Under protective atmosphere, the experiment was carried out at a set heating rate, and the pressure difference between the upper and lower layers, the slag iron dripping temperature and the dripping time were recorded.
[0031] Preferably, the comprehensive index of air permeability is calculated by the following formula:
[0032]
[0033] Among them, ΔP T is the pressure difference of the material layer at different temperatures, ΔP1 is the pressure difference of the material layer when the first drop of slag iron drips, T1 is the temperature at which the first drop of slag iron drips, and T2 is the temperature at which the slag iron completely drips.
[0034] Preferably, the mass loss of the coke sample is calculated by the following formula:
[0035]
[0036] Among them, m0 is the mass of coke before reaction, and m1 is the remaining mass of coke after reaction.
[0037] Preferably, the strength retention rate is calculated by the following formula:
[0038]
[0039] Among them, m1 is the remaining mass of coke after the reaction, and m2 is the mass of coke with a particle size greater than 10 mm after the drum test.
[0040] The invention provides a method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process.
[0041] It has the following beneficial effects:
[0042] 1. The present invention combines the dissolution test with the slag iron coke penetration test to quantitatively analyze the dissolution behavior of coke in a hydrogen-rich atmosphere and its performance changes under high temperature and molten slag iron. By calculating the coke weight loss rate, strength retention rate and permeability comprehensive index, the reaction resistance, mechanical property retention ability and permeability of the coke are fully characterized.
[0043] 2. The present invention can quantify the effect of coke on the fluidity of slag iron and the permeability of blast furnace charge layer by analyzing the comprehensive index of coke permeability. Combined with the charge composition and the actual working conditions of the blast furnace, the adaptability of coke is evaluated to ensure the matching degree of coke and charge composition. This method provides a scientific reference for the optimization of blast furnace operation and the promotion of low-carbon smelting technology.
[0044] 3. The present invention can simulate the actual reaction environment of coke in a hydrogen-rich atmosphere of a blast furnace and reveal the deterioration law of coke in a high-hydrogen atmosphere. By quantitatively analyzing the changes in coke performance, the present invention can guide the selection of coke quality and the improvement of production processes, help reduce coke consumption, and improve hydrogen utilization efficiency. This technology provides key technical support for the steel industry to achieve green and low-carbon transformation BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a schematic diagram of the method flow of the present invention;
[0046] Figure 2 It is a schematic diagram of the structure of the dissolution experiment device of the present invention;
[0047] Figure 3 It is a schematic structural diagram of the slag iron coking experimental device of the present invention. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Please see attached Figure 1 -Attached Figure 3 The present invention provides a method for evaluating the degree of coke quality deterioration during blast furnace hydrogen-rich smelting. The method combines a dissolution loss experiment with a slag-iron coke penetration experiment to quantitatively analyze the performance degradation characteristics of coke in a hydrogen-rich atmosphere. The method also combines the blast furnace charge composition and operating conditions to comprehensively evaluate the adaptability of the coke quality.
[0050] like Figure 1 As shown, the method for evaluating the degree of coke quality degradation in a blast furnace hydrogen-rich smelting process may include the following steps:
[0051] S1. Under the conditions of simulating the hydrogen-rich atmosphere of a blast furnace, a dissolution test device is used to perform a gasification reaction on a coke sample, the mass loss of the coke sample is controlled to reach a set range, and the coke sample after the reaction is obtained;
[0052] S2. Using a slag iron coke penetration test device to conduct a slag iron coke penetration test on the coke sample after the reaction, and measuring the air permeability, slag iron dripping time and strength retention rate of the coke coke penetration process;
[0053] S3. Based on the data obtained from the dissolution test and the slag iron coke penetration test, the coke performance is quantitatively evaluated using the coke weight loss rate, strength retention rate and permeability comprehensive index.
[0054] Each step of the method of the present invention is described in detail below.
[0055] Step S1, the dissolution experiment step, is used to simulate the reaction behavior of coke under blast furnace hydrogen-rich smelting conditions. Specifically, the coke sample is subjected to gasification reaction through a dissolution experiment device to control the mass loss of the coke sample to reach a set range.
[0056] In this embodiment, the dissolution experiment device includes the following components:
[0057] A high temperature furnace, wherein a hanging basket and a thermocouple for placing coke samples are arranged in the high temperature furnace;
[0058] Thermobalance, located on the top of the high-temperature furnace, is connected to the coke sample through a hanging basket and is used to monitor the mass change of the coke sample in real time;
[0059] A gas supply system, which includes multiple gas cylinders for providing nitrogen (N2), carbon monoxide (CO), carbon dioxide (CO2) and hydrogen (H2), with the purity of the gas not less than 99.99%;
[0060] A water vapor generator, which provides liquid water in a quantitative manner through a peristaltic pump and forms water vapor through heating and gasification;
[0061] A gas mixing device is connected between the gas supply system and the high-temperature furnace, and is used to mix water vapor and other gases in a set ratio and then transport them to the high-temperature furnace;
[0062] The control system is connected with the high temperature furnace, the thermobalance and the gas supply system, and is used to set the experimental heating rate, the experimental temperature and the gas flow ratio, and to record the experimental data in real time through the thermobalance.
[0063] like Figure 2 As shown, in a preferred embodiment of the present invention, the dissolution experiment device comprises:
[0064] Computer 1 is used to control experimental parameters and data collection, and is connected with the high temperature furnace, the thermobalance and the gas supply system to realize the automatic control and data recording of the whole experiment.
[0065] Thermocouple 2 is installed inside the high-temperature furnace to monitor the temperature inside the furnace in real time, ensure the precise control of the experimental temperature, and adjust the heating power through the control system.
[0066] The water vapor generator 4 is connected to the gas mixing device and is used to quantitatively gasify the liquid water 3 to generate water vapor. The water supply is achieved through a peristaltic pump, and the water vapor is transported to the gas mixing tank to mix with other gases.
[0067] The thermobalance 5 is located on the top of the high temperature furnace and is connected to the coke sample 7 through a hanging basket. It is used to measure the mass change of the coke sample in real time and transmit the data to the computer for recording and calculation.
[0068] The corundum tube 6, as the reaction chamber of the high-temperature furnace, has an inner wall with high-temperature resistance and corrosion resistance, and is used to accommodate samples and provide a high-temperature environment required for the experiment.
[0069] The furnace heating body 8 uses MoSi2 rods as heating elements and is installed inside the high-temperature furnace. The heating power is controlled by a computer to achieve precise adjustment of the temperature range, and the highest heating can reach 1873K.
[0070] The corundum balls 9 are filled in the bottom of the corundum tube to support the coke sample 7, ensuring that the gas passes through the sample layer evenly, thereby improving the stability of the experiment and the accuracy of the data.
[0071] The heating pipeline 10 connects the gas mixing device 11 and the high-temperature furnace. The pipeline heating method ensures that the mixed gas maintains the set temperature before entering the high-temperature furnace to avoid fluctuations in the experimental atmosphere.
[0072] The heating gas mixing tank 11 is connected to the gas supply system and the high-temperature furnace, and is used to mix nitrogen (N2), carbon monoxide (CO), carbon dioxide (CO2), hydrogen (H2) and water vapor in proportion, heat them, and transport them to the high-temperature furnace through the heating pipeline.
[0073] The gas supply system includes a nitrogen cylinder 12, a carbon monoxide cylinder 13, a carbon dioxide cylinder 14 and a hydrogen cylinder 15. The purity of the gases is not less than 99.99%. The gases are transported to the heating gas mixing tank after being controlled by a pressure reducing valve and a flow meter to ensure accurate regulation of gas composition and flow.
[0074] In this embodiment, the specific steps of the dissolution experiment include:
[0075] First, the coke sample was pretreated, and a spherical coke sample with a particle size of 16 mm was selected and weighed 100 g. The weighed coke sample was placed in the hanging basket of the high-temperature furnace to ensure that the sample was evenly distributed and facilitated sufficient contact with the gas.
[0076] Subsequently, nitrogen (N2) was introduced into the high-temperature furnace as a protective atmosphere through the gas supply system, and the nitrogen flow rate was controlled within the range of 5L / min to avoid unnecessary oxidation reaction of the coke during the heating process. During this process, the heating rate of the high-temperature furnace was set to 10K / min through the control system, and the temperature was gradually increased to 1100℃. During the heating process, the temperature in the furnace was monitored in real time by a thermocouple, and the heating power was adjusted by the control system to keep the temperature stable.
[0077] When the temperature in the high-temperature furnace reaches 1100°C, nitrogen is continuously introduced and the temperature is kept constant for 20 minutes to stabilize the experimental environment and ensure that the surface temperature of the coke sample is consistent with the furnace temperature. After the temperature is stabilized, a mixed gas of a set ratio is introduced into the gas mixing device through the gas supply system. The mixed gas includes hydrogen (N2), carbon monoxide (CO), carbon dioxide (CO2) and water vapor (H2O). The ratio is adjusted according to the actual operating conditions of the blast furnace, and the total gas flow rate is set to 5L / min.
[0078] Water vapor is quantitatively injected into the water vapor generator through a peristaltic pump, and mixed with other gases after heating and gasification, and uniformly transported to the high-temperature furnace by the gas mixing device to form an experimental environment simulating the hydrogen-rich atmosphere of the blast furnace. The specific adjustment of the mixed gas ratio can be based on the application of hydrogen-rich technology in blast furnace smelting, such as the gas composition when the water vapor ratio is 0%-20%.
[0079] After the atmosphere stabilizes, the weight loss data of the coke sample is recorded. The thermobalance monitors the changes in the coke mass in real time through the connection with the hanging basket, and transmits the data to the control system, which dynamically calculates the weight loss rate of the coke. The weight loss rate calculation formula of the coke is as follows:
[0080]
[0081] Wherein, m0 is the initial mass of the coke sample before the experiment, and m1 is the remaining mass of the coke sample after the experiment, in g.
[0082] When the weight loss rate of the coke sample reaches 25%, the control system stops the supply of the mixed gas and resumes the nitrogen protection. Subsequently, the heating function of the high-temperature furnace is turned off by the control system, and the temperature in the high-temperature furnace is gradually cooled at a cooling rate of 5K / min, and the nitrogen atmosphere is maintained to avoid secondary oxidation reaction of the coke during the cooling process.
[0083] After the experiment is completed, the coke sample cooled to room temperature is taken out and kept for use in the subsequent slag iron coking experiment.
[0084] In this embodiment, the dissolution experiment can fully simulate the gasification reaction behavior of coke in a hydrogen-rich atmosphere of a blast furnace, and obtain the coke samples after dissolution under different atmosphere conditions and the time required for the dissolution rate to reach 25%. This experiment provides an important basis for analyzing the reaction performance and degradation characteristics of coke in a hydrogen-rich environment.
[0085] For step S2, in this embodiment, the slag iron coke penetration experiment is used to simulate the performance change of coke under the condition of the blast furnace dripping zone. The experiment quantitatively analyzes the performance of coke under the combined effect of slag iron and high temperature atmosphere by measuring the air permeability of coke, the slag iron dripping time, and the dissolution loss rate and strength retention rate of coke after the reaction, and provides a scientific basis for the matching of coke and furnace charge.
[0086] In this embodiment, the device used in the slag iron coking experiment includes the following components:
[0087] High-temperature coke oven: The high-temperature coke oven is the main heating equipment for the experiment. It has built-in silicon-molybdenum rods as heating elements, and the maximum temperature can reach 1873 K. The coke oven is equipped with a thermocouple to monitor the temperature in the oven in real time and accurately adjust the heating power through connection with the temperature control system.
[0088] Perforated crucible: The bottom of the perforated crucible is provided with a coke hole for placing coke samples and slag iron mixture in layers to ensure that the molten slag iron can drip smoothly. The crucible is made of molten corundum and has excellent high temperature tolerance and corrosion resistance.
[0089] Pressure sensor: The pressure sensors are respectively installed at the upper and lower parts of the coke layer to monitor the pressure difference between the upper and lower parts of the layer in real time. The pressure sensor is connected to the data acquisition device through a pipeline to ensure that the dynamic changes of the air permeability of the layer can be recorded in real time during the experiment.
[0090] Data acquisition device: connected with the pressure sensor and temperature control system, used to collect and record experimental data such as pressure difference of material layer, slag iron dripping time and temperature during the coking process. The data acquisition device is connected with the computer to ensure the integrity of experimental data storage and subsequent analysis.
[0091] Gas supply system: including nitrogen cylinders with nitrogen purity not less than 99.99%. The gas flow is controlled by a pressure reducing valve and a flow meter and is used for experimental protective atmosphere.
[0092] Temperature control system: connected with the high-temperature coke oven, it controls the stability of the experimental heating process by presetting the heating rate to ensure accurate and controllable experimental conditions.
[0093] like Figure 3 As shown, in a preferred embodiment of the present invention, the slag iron coking experimental device comprises:
[0094] Gas supply cylinder 16: used to provide experimental protective atmosphere, the gas is nitrogen (N2), the purity of which is not less than 99.99%. The gas is controlled by a pressure reducing valve and a flow meter, and is transported to the bottom inlet of the high-temperature coke oven through a pipeline.
[0095] Pressure gauge 17: installed on the pipeline of the gas supply system, used to monitor the pressure of the gas supply in real time to ensure the stability of the experimental atmosphere.
[0096] Gas outlet 18: It is arranged at the top of the high-temperature coke oven and is used to discharge the gas generated during the experiment to maintain the gas flowability and pressure stability in the coke oven.
[0097] Thermocouple 19: It is set inside the high-temperature coke oven and is used to monitor the temperature inside the coke oven in real time. The thermocouple is connected to the temperature control system to transmit the measured temperature data to the control system to achieve accurate regulation and feedback control of the temperature inside the oven.
[0098] Crucible 20: The crucible is made of molten corundum material and has high temperature resistance and chemical corrosion resistance. The crucible is used to contain the coke sample 22 and the slag iron sample 21.
[0099] Coke sample 22: It is a coke sample that has been processed by a dissolution experiment and is evenly layered on the bottom of the crucible to simulate the support and coke penetration performance of coke in the dripping zone of a blast furnace.
[0100] Slag sample 21: It is a mixture of metallic iron powder and pre-melted slag powder, evenly spread on top of the coke sample to simulate the interaction between molten slag and coke under the conditions of the blast furnace dripping zone.
[0101] Slag dripping hole 23: It is arranged at the bottom of the crucible and is used for the molten slag to drip, simulating the fluidity process of slag in the dripping zone of the blast furnace, and recording the dynamic changes in the dripping process through a camera.
[0102] Heating element 24: installed inside the high-temperature coke oven, using silicon-molybdenum rods as heating elements, capable of providing a heating temperature of up to 1873 K. The heating element adjusts the heating power through a temperature control system to ensure the stability of the heating rate.
[0103] The crucible 25 is located directly below the slag iron dripping hole and is used to receive the molten slag iron sample to prevent the dripping from damaging the internal structure of the experimental device and facilitate the collection and analysis of samples after the experiment.
[0104] Camera 26: installed on the outside of the high-temperature coke oven, monitors the experimental process in real time through the observation window, and is used to record the dripping dynamics of the molten slag and the changes in the sample layer.
[0105] Pressure sensors 27: respectively arranged above and below the crucible, for real-time monitoring of the upper and lower pressure differences of the coke sample layer. The pressure sensors are connected to a computer 28 via a data line to achieve data collection and real-time transmission.
[0106] Computer 28: connected with the pressure sensor, thermocouple and camera, used to record and store experimental data, including information such as pressure difference of material layer, temperature, slag iron dripping time and permeability change curve.
[0107] Control cabinet 29: connected with the temperature control system and the heating body, used to set the heating rate and the experimental time, and realize the centralized management and operation of the experimental equipment.
[0108] In this embodiment, the specific implementation steps of the slag iron coking experiment are as follows:
[0109] The coke samples after the dissolution test were used as experimental materials and were first pretreated. The coke samples were evenly layered and laid on the bottom of the perforated crucible to ensure the uniform flow of gas and molten slag during the experiment. A mixture of 300g of metallic iron powder and blast furnace slag powder was added above the coke samples. The slag system composition was prepared according to the actual slag system composition when the reduction degree of the blast furnace iron-containing charge reached 80%.
[0110] At the beginning of the experiment, a perforated crucible was placed inside a high-temperature coke oven, and nitrogen was introduced into the oven through a gas supply system to provide a protective atmosphere, with the nitrogen flow rate controlled within the range of 5L / min. Subsequently, the temperature was gradually increased at a set heating rate (10K / min). During this process, the temperature changes inside the coke oven were monitored in real time by a thermocouple, and the data was fed back to the temperature control system to ensure the stability and accuracy of the temperature inside the oven.
[0111] As the temperature in the furnace gradually rises, the molten slag gradually drips. The pressure sensor records the dynamic changes of the pressure difference of the material layer during the coking process in real time, and the data acquisition device records the pressure difference at each moment (ΔP T At the same time, the temperature of the molten slag when it first drips (T1) and the temperature when it completely drips (T2) are recorded, and the time required for the entire dripping process is calculated.
[0112] During the experiment, the change of coke permeability was characterized by the comprehensive permeability index (TPI), and the calculation formula was:
[0113]
[0114] Among them, ΔP Tis the pressure difference of the material layer at different temperatures, ΔP1 is the pressure difference of the material layer at time T1, T1 is the temperature at which the molten slag first drips, and T2 is the temperature at which the molten slag completely drips. The comprehensive permeability index can be used to quantitatively evaluate the effect of coke on the permeability of slag and the permeability of blast furnace material column.
[0115] After the experiment, the coke samples after the coking reaction were taken out for subsequent analysis. The coke samples were first weighed to calculate the weight loss rate during the reaction. Then, the mass of particles with a diameter greater than 10 mm in the coke samples after the reaction was measured through a drum test, and the strength retention rate of the coke was calculated using the following formula:
[0116]
[0117] Among them, m1 is the remaining mass of coke after the reaction, and m2 is the mass of coke with a particle size greater than 10 mm after the drum test.
[0118] In this embodiment, the slag iron coke penetration experimental device and its experimental process are fully disclosed, which can realize the performance analysis of coke samples under the combined effects of high temperature and molten slag iron. Through the comprehensive evaluation of the permeability comprehensive index, dripping time and strength retention rate, the high-temperature performance of coke can be fully quantified, providing a reliable experimental basis for the selection of coke quality and the matching of furnace charge in the blast furnace ironmaking process.
[0119] For step S3, in this embodiment, based on the data obtained from the dissolution test and the slag iron coke penetration test, the coke weight loss rate, strength retention rate and permeability comprehensive index are used to quantitatively evaluate the performance of the coke, so as to comprehensively analyze the behavioral characteristics and adaptability of the coke under the conditions of blast furnace hydrogen-rich smelting. Among them, the control of the coke weight loss rate is intended to provide a coke sample with a weight loss rate of 25% for the slag iron coke penetration test.
[0120] In this embodiment, the weight loss rate of coke is regulated by dissolution test to ensure that the weight loss rate of the coke sample obtained by the experiment is 25%. The calculation formula of the weight loss rate is shown in the above steps.
[0121] In the present invention, the weight loss rate of coke is controlled to 25% to ensure that the sample conditions of the subsequent slag iron coke penetration test are consistent. The reaction resistance of coke can be indirectly evaluated by the length of time required for coke to reach 25% weight loss rate in the dissolution loss test, but the main purpose of the present invention is to provide uniform sample conditions for the slag iron coke penetration test, rather than to compare the weight loss rates of different samples.
[0122] In this embodiment, the comprehensive performance of coke under high temperature and molten slag iron conditions is further evaluated by using the slag iron coke penetration experiment. The coke sample with a weight loss rate of 25% is used as the experimental material in the experiment. The permeability change curve of the material layer is recorded in the coke penetration experiment to analyze the fluidity of the molten slag iron and the supporting capacity of the coke. The mechanical property retention rate of the coke after the reaction is determined by the drum experiment, and its calculation formula is shown in the above steps.
[0123] In this embodiment, the data obtained by the above method comprehensively analyzes the permeability, mechanical strength and effect on the fluidity of slag iron of the coke, providing a reliable basis for the evaluation of the high temperature performance of the coke. It should be particularly noted that the weight loss rate of the coke in the present invention is 25%, the purpose of which is to ensure the consistency of the experimental conditions, rather than to compare the weight loss rates of different coke samples. If it is necessary to analyze the reaction resistance of the coke, it can be indirectly evaluated by the length of time required for the sample to reach a weight loss rate of 25% in the dissolution experiment, but this process does not belong to the core purpose of the present invention.
[0124] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for evaluating the degree of deterioration of coke quality during blast furnace hydrogen-rich smelting, characterized in that: The following steps are involved: Under the conditions of simulating the hydrogen-rich atmosphere of a blast furnace, a dissolution test device is used to perform a gasification reaction on the coke sample, the mass loss of the coke sample is controlled to reach a set range, and the coke sample after the reaction is obtained; The coke samples after reaction were subjected to slag iron coke penetration test using slag iron coke penetration test device to measure the permeability, slag iron dripping time and strength retention rate of the coke coke penetration process; Based on the data obtained from the dissolution test and the slag iron coke penetration test, the coke performance was quantitatively evaluated using the coke weight loss rate, strength retention rate and permeability comprehensive index.
2. A method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process according to claim 1, characterized in that: The dissolution experiment device comprises: A high temperature furnace, in which a hanging basket for accommodating coke samples is arranged, and a gas mixing device is connected to the outside; Thermobalance, which is set on the top of the high-temperature furnace and connected to the hanging basket, is used to measure the mass change of the coke sample in real time; A first gas supply system, comprising a plurality of gas sources and a water vapor generator, wherein the first gas supply system is connected to a gas mixing device via a pipeline; A gas mixing device is provided between the first gas supply system and the high temperature furnace, and is used to mix each gas source and water vapor and then transport them to the high temperature furnace; The control system is connected with the high temperature furnace and the gas supply system to control the temperature, atmosphere composition and flow rate.
3. The method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process according to claim 2, characterized in that: The dissolution experiment comprises the following steps: The coke sample is placed in the hanging basket of the dissolution experiment device and a protective atmosphere is set; At a predetermined temperature, a mixed gas is introduced, wherein water vapor is provided by a water vapor generator and mixed with other gases; The mass change of the coke is recorded in real time. When the weight loss rate reaches a predetermined value, the experiment is stopped and the coke is cooled for future use.
4. The method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process according to claim 1, characterized in that: The slag iron coking experimental device comprises: A high-temperature coke oven, in which a crucible for containing coke samples and slag-iron mixture is arranged; A perforated crucible with a coke hole at the bottom for placing the layered coke sample and the slag-iron mixture above it; Pressure sensor, used to monitor the pressure difference of the coke layer in real time; The data acquisition device is connected with the pressure sensor and the temperature control system to record the pressure change of the material layer, the temperature and time of the slag dripping; The second gas supply system is used to provide a protective atmosphere and is connected to the high-temperature coke oven through a pipeline; The temperature control system is connected to the high-temperature coke oven and is used to control the heating rate and experimental temperature.
5. A method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process according to claim 4, characterized in that: The slag iron coking experiment includes the following steps: The dissolved coke sample is spread in layers in a perforated crucible; A mixture of metallic iron powder and pre-melted slag powder is laid on top of the coke sample; Under protective atmosphere, the experiment was carried out at a set heating rate, and the pressure difference between the upper and lower layers, the slag iron dripping temperature and the dripping time were recorded.
6. The method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process according to claim 1, characterized in that: The comprehensive index of air permeability is calculated by the following formula: Among them, ΔP T is the pressure difference of the material layer at different temperatures, ΔP1 is the pressure difference of the material layer when the first drop of slag iron drips, T1 is the temperature at which the first drop of slag iron drips, and T2 is the temperature at which the slag iron completely drips.
7. The method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process according to claim 1, characterized in that: The coke weight loss rate is calculated by the following formula: Among them, m0 is the mass of coke before reaction, and m1 is the remaining mass of coke after reaction.
8. The method for evaluating the degree of deterioration of coke quality in a blast furnace hydrogen-rich smelting process according to claim 1, characterized in that: The strength retention rate is calculated by the following formula: Among them, m1 is the remaining mass of coke after the reaction, and m2 is the mass of coke with a particle size greater than 10 mm after the drum test.
Citation Information
Patent Citations
Determination method for degradation process of coke for hydrogen-rich blast furnace
CN115032113A
Coke iron oxide coupling performance determination method
CN117214032A
Method for measuring reduction performance and mechanical performance of coke in simulated blast furnace environment
CN117451567A
Iron ore and coke coupling metallurgical performance detection device and detection method
CN118392914A
Method of determination of full melt outlet during blast-furnace smelting
RU2558840C1